2018
DOI: 10.3390/nu10080967
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum Zinc Levels in Patients with Multiple Sclerosis Compared to Healthy Controls

Abstract: Objective: Diminished blood levels of zinc have been reported to be associated with T-cell-mediated autoimmunity, which has been implicated in multiple sclerosis (MS). We aimed to compare the distribution of serum zinc status in MS patients with that in healthy controls (HCs) and to investigate a potential correlation with clinical state, through analysis of serum zinc concentration in MS patients suffering from different disease subtypes. Methods: Serum zinc concentrations of 133 patients with relapsing (RMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…The zinc mean consumption value was 29.5% lower in the MS group compared with controls, below the DRI recommendation. These findings are consistent with lower serum zinc levels in MS patients previously published [ 20 , 22 ]. Of relevance, in the CNS, zinc plays roles in modifying neuronal excitability and synaptic plasticity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The zinc mean consumption value was 29.5% lower in the MS group compared with controls, below the DRI recommendation. These findings are consistent with lower serum zinc levels in MS patients previously published [ 20 , 22 ]. Of relevance, in the CNS, zinc plays roles in modifying neuronal excitability and synaptic plasticity.…”
Section: Discussionsupporting
confidence: 93%
“…This is of particular interest as metal homeostasis plays a critical role in regulation of the CNS and is essential for normal functioning. Moreover, metal deficiencies have been found in serum of MS patients, specifically iron, magnesium, lithium, and zinc [ 17 , 18 , 19 , 20 ], and metal imbalances have been linked to demyelination, perhaps involving oxidative stress [ 21 ]. The zinc mean consumption value was 29.5% lower in the MS group compared with controls, below the DRI recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Pawlitzki and colleagues found that MS patients had a significantly lower concentrations of zinc compared to healthy controls but there was no significant relationship between serum zinc and either disease duration, median number of relapses, annual relapse rate, or EDSS [15].…”
Section: Discussionsupporting
confidence: 90%
“…Our results for Cu, Fe and Zn agree with those observed by Alimonti et al 9, who showed a decreased concentration in the blood of MS patients. Pawlitzki et al 18 also found lower serum zinc levels in patients with multiple sclerosis. However, Janghorbani et al 13 and Visconti et al 19 found an increase in the levels of these metallic elements in the serum of MS subjects.…”
Section: Resultsmentioning
confidence: 91%